Muharram marriage in ancient Iranian society: From Ilam to the end of the Sasanian Empire (Raparin Journal of Humanities (RJH), 2024)
Muharram marriage is one of the most common social and cultural issues in ancient Iranian history. It has been a subject of debate among researchers and has divided them into several groups. There is a difference in the definition of the concept of Muharram in the civilization cultures. In the religious texts of the Avesta and Pahlavi languages, this type of marriage is known as "blood and death". It was popular among the royal family for centuries after the advent of Christianity and the end of the Sassanid Empire and later Islam, but with the advent of these two religions, it completely faded and ended. It is worth mentioning that this process was carried out under the influence of mythical and religious thoughts، and was the reason for its spread. Each of the ancient states of Iran (Elamite, Achaemenid, Ashkanid, and Sassanid) gave it legitimacy and considered it as the reason for preserving the sacred blood and maintaining sovereignty within the royal family, their kings married their mothers، sisters and daughters. And then with the advent of the Zoroastrian religion, Moghan of the religion, they further sanctified it and marriage was defined as "holy marriage", although mythological texts had a special influence and role in continuing this issue, although it was found out in religious texts that Zoroaster as the prophet of the religion in a conversation with the god (Ahura Mazda) considered this type of marriage inappropriate and denied it. However, religious men and legends have left an influence in the continuation of this marriage until the end of the Sassanid Empire and can be seen in ancient Iranian civilizations. The research is entitled Muharram Marriage in Ancient Iranian Society from Ilam to the End of the Sassanid Empire. It is an analytical and historical study consisting three themes (Topic 1 / A view of Muharram marriage, in general and in the myths of ancient Iran in particular. Topic 2 / Muharram marriage in the ruling states of ancient Iran (Ilam, Achaemenid, Ashkani, Sassanid), Topic 3/ Muharram marriage according to Zoroastrian religious beliefs).